Valproic Acid Suppresses Autoimmune Recurrence and Allograft Rejection in Islet Transplantation through Induction of the Differentiation of Regulatory T Cells and Can Be Used in Cell Therapy for Type 1 Diabetes - Jeng-Rong Lin; Shing-Hwa Huang; Chih-Hsiung Wu; Yuan-Wu Chen; Zhi-Jie Hong; Chia-Pi Cheng; Huey-Kang Sytwu; Gu-Jiun Lin (MDPI AG, 2021)
Type 1 diabetes mellitus (T1D) results from the destruction of insulin-producing β cells in the islet of the pancreas by lymphocytes. Non-obese diabetic (NOD) mouse is an animal model frequently used for this disease. It has been considered that T1D is a T cell-mediated autoimmune disease. Both CD4+ and CD8+ T cells are highly responsible for the destruction of β cells within the pancreatic islets of Langerhans. Previous studies have revealed that regulatory T (Treg) cells play a critical role in the homeostasis of the immune system as well as immune tolerance to autoantigens, thereby preventing autoimmunity. Valproic acid (VPA), a branched short-chain fatty acid, is widely used as an antiepileptic drug and a mood stabilizer. Previous reports have demonstrated that VPA treatment decreases the incidence and severity of collagen-induced arthritis and experimental autoimmune neuritis by increasing the population of Treg cells in these mouse disease models. Given the effect of VPA in the induction of Treg cells' population, we evaluated the therapeutic potential and the protective mechanism of VPA treatment in the suppression of graft autoimmune rejection and immune recurrence in syngeneic or allogenic islet transplantation mouse models. In our study, we found that the treatment of VPA increased the expression of forkhead box P3 (FOXP3), which is a critical transcription factor that controls Treg cells' development and function. Our data revealed that 400 mg/kg VPA treatment in recipients effectively prolonged the survival of syngeneic and allogenic islet grafts. The percentage of Treg cells in splenocytes increased in VPA-treated recipients. We also proved that adoptive transfer of VPA-induced Tregs to the transplanted recipients effectively prolonged the survival of islet grafts. The results of this study provide evidence of the therapeutic potential and the underlying mechanism of VPA treatment in syngeneic islet transplantation for T1D. It also provides experimental evidence for cell therapy by adoptive transferring of in vitro VPA-induced Tregs for the suppression of autoimmune recurrence.